The analogy and typologization in comparative historical and legal research - Шигаль, Д. А. (Problems of legality, 2015)
This article examines the interaction of comparative historical and legal method and such means of scientific knowledge as analogy and typologization. Terms of analogy and typologization use during a comparative study on the historical and legal theme are analysed in the article. Findings about gnosiological potential of analogy and typologization in the comparative historical and legal analysis are made.